Nitrous Oxide sedation for intra-articular injection in juvenile idiopathic arthritis - Harel Liora; Press Joseph; Tauber Tsivia; Rothschild Michal; Chapnick Gil; Uziel Yosef; Hashkes Philip J (BMC, 2008)
Abstract Background Intra-articular corticosteroid injection in juvenile idiopathic arthritis (JIA) is often associated with anxiety and pain. Recent reports advocate the use of nitrous oxide (NO), a volatile gas with analgesic, anxiolytic and sedative properties. Objective To prospectively evaluate the effectiveness and safety of NO analgesia for intra-articular corticosteroid injection in JIA, and to assess patients and staff satisfaction with the treatment. Methods NO was administered to JIA patients scheduled for joint injection. The patient, parent, physician and nurse completed visual-analog scores (VAS) (0-10) for pain, and a 5-point satisfaction scale. Change in heart rate (HR) during the procedure was recorded in order to examine physiologic response to pain and stress. Patient's behavior and adverse reactions were recorded. Results 54 procedures (72 joints) were performed, 41 females, 13 males; 39 Jewish, 13 Arab; mean age was 12.2 ± 4.7 year. The median VAS pain score for patients, parents, physicians and nurses was 3. The HR increased ≥ 15% in 10 patients. They had higher VAS scores as evaluated by the staff. The median satisfaction level of the parents and staff was 3.0 and 5.0 respectively. Adverse reactions were mild. Conclusion NO provides effective and safe sedation for JIA children undergoing intra-articular injections.